Subcentral Taxation in Spain - Guerre, Asuncion Arner (International Journal of Economics and Financial Issues, 2022)
The latest reform of the Financing System of the Autonomous Communities of the common regime (AFS) has deepened Spain’s fiscal co-responsibility and financial autonomy. In the Personal Income Tax, the income transfer has been accompanied by a growing regulatory capacity, creating a regional personal income tax (RPIT). Subsequently, Autonomous Communities must approve yearly an autonomous rate. Regional governments get the RPIT income by monthly payments on account (POA) based on the budget forecast for the following year on fractional payments and withholdings. Subsequently, there is the corresponding final settlement two years later. This work aims to study the RPIT from the POA, considering the potential and current taxation to evaluate possible inefficiencies. The methodology consists of estimating a Dynamic Panel Data of the fifteen Autonomous Communities for 2003-2019, using GMM. Results show that there was some degree of tax base overlap between levels of government in the Personal Income Tax. Besides, there was some type of reaction of the tax rate in one region to the tax rate of others. Consequently, the State transfers internalized vertical and horizontal externalities. In addition, efficiency concerns mainly were about taxation for entrepreneurs.